2006
DOI: 10.1097/01.cad.0000217425.44584.9f
|View full text |Cite
|
Sign up to set email alerts
|

Lack of usefulness of epidermal growth factor receptor expression determination for cetuximab therapy in patients with colorectal cancer

Abstract: In patients with metastatic colorectal cancer, the use of cetuximab currently requires a documented tumoral epidermal growth factor receptor positivity. Responses to cetuximab, however, have been described in patients with epidermal growth factor receptor-negative tumors. We have used cetuximab in all eligible patients with metastatic colorectal cancer, whether their tumor expressed epidermal growth factor receptor or not. We assessed the cetuximab efficacy with regard to tumoral epidermal growth factor recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(63 citation statements)
references
References 11 publications
4
58
0
1
Order By: Relevance
“…Most studies on ovarian cancer and HER2 have evaluated the HER2 protein expression by immunohistochemistry and fluorescence in situ hybridization (FISH) with a high reported concordance between these two methods (18,19). Nevertheless, immunohistochemistry is only semi-quantitative and for HER1 there are severe difficulties in predicting response to anti-HER1 therapies by HER1 immunohistochemical testing (20)(21)(22)(23). To our knowledge, this is the first study that describes quantitative levels of all four receptors of the EGF receptor family in ovarian cancer as well as their gene expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on ovarian cancer and HER2 have evaluated the HER2 protein expression by immunohistochemistry and fluorescence in situ hybridization (FISH) with a high reported concordance between these two methods (18,19). Nevertheless, immunohistochemistry is only semi-quantitative and for HER1 there are severe difficulties in predicting response to anti-HER1 therapies by HER1 immunohistochemical testing (20)(21)(22)(23). To our knowledge, this is the first study that describes quantitative levels of all four receptors of the EGF receptor family in ovarian cancer as well as their gene expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Recent retrospective studies Hebbar et al, 2006) confirmed activity of CxIri or Cx alone in EGFR negative mCRC, and the practice of testing EGFR status by IHC to select for Cx (or Pa) therapy is clearly inappropriate and other predictive tests are needed (Meropol, 2005;Nygren et al, 2005;Hecht et al, 2006b). Furthermore, the expression in primary tumors does not necessarily reflect or predict the expression in metastatic sites (Scartozzi et al, 2004).…”
Section: Predicting Efficacy Of CX and Pamentioning
confidence: 99%
“…Likewise, NSCLC patients overexpressing EGFR have been demonstrated to have a worse outcome (14). Furthermore, current evidence suggests no association between a high EGFR cell surface expression and cetuximab response in colorectal cancer patients (15)(16)(17)(18)(19). Particularly in colorectal cancer, recent studies suggest that mutations of K-RAS gene are associated with nonresponsiveness to cetuximab, while amphiregulin and epiregulin overexpression may be markers of response (20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 94%